2022
DOI: 10.3389/fnut.2021.792793
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia nilotica Head Lipids Improved Bone Loss by Regulating Inflammation and Serum Metabolism Through Gut Microbiota in Ovariectomized Rats

Abstract: Osteoporosis is a global health problem, and it is of great significance to replace the drugs with natural functional factors. In this study, we investigated the antiosteoporotic activity of lipids prepared from Tilapia nilotica fish head lipids (THLs) in the ovariectomized osteoporosis rats. THLs are composed of neutral lipids (NL, 77.84%), phospholipids (PL, 11.86%), and glycolipids (GL, 6.47%). There were apparent differences in the fatty acid composition of disparate components, and PL contains the most ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…The 3D images of coronal were constructed. The BMD, trabecular number (Tb.N), trabecular thickness (Tb.Th), and trabecular separation (Tb.Sp) were calculated by the tomography software ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…The 3D images of coronal were constructed. The BMD, trabecular number (Tb.N), trabecular thickness (Tb.Th), and trabecular separation (Tb.Sp) were calculated by the tomography software ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…After that, the membranes were soaked in ECL chemiluminescence solution to detect the target protein blots which were visualized by ImageQuant LAS4000mini system (GE, Boston, MA, USA). During the whole process, β-actin was treated as a control protein [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a study using an ovariectomized osteoporosis rat model, Tilapia nilotica fish head lipids (THLs) significantly reduced the levels of Alistipes in the gut, while increasing the abundance of beneficial bacteria, and suggested that THLs may be a functional factor with antiosteoporotic activity. THLs are also rich in docosahexaenoic acid, which has been shown to regulate the intestinal microbiota and promote bone formation ( Che et al., 2021 ; Zhu et al., 2021 ).…”
Section: Interventions With Specific Gut Microbiota To Improve Bone H...mentioning
confidence: 99%